Spatial analysis of the tourism supply, in Portugal, at NUTs III level - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The tourism in Portugal has been an important contribution to the economic development of the country, namely in zones where is difficult to implement others activities, specifically the manufacturing. The objective of this work is to analyze, for the period 2002-2011, with spatial econometric techniques (using the GeoDa informatics program), the statistic data, available in the Statistics Portugal (INE), of some variables related with the tourism in the NUTs III of Portugal Continental, namely: capacity (N.) in accommodation establishments; capacity in accommodation establishments per 1000 inhabitants (N.); nights (N.) in accommodation establishments; nights in accommodation establishments per 100 inhabitants (N.); accommodation establishments (N.); average stay (N.) in accommodation establishments; customers (N.) in accommodation establishments; proportion of foreign customers (%); and net rate of bed occupancy (%) in accommodation establishments. The first, third, fifth, sixth, seventh and ninth variables were further disaggregated for the several forms of accommodation establishments, as following: all accommodation establishments; hotels; pensions; guesthouses; inns; motels; hotels-apartments; holiday villages; and tourist apartments. The data was used in average and the econometric analyses were cross section. There are some signs of spatial autocorrelation in some variables and some forms of accommodation establishments.
Keywords: C21; L83; O18; 330; Spatial econometrics; Tourism supply; Portuguese NUTs III